Heath James, Eighteenth Century Penal Theory, Oxford University Press, 1963 - Salmonowicz, Stanisław (Czasopismo Prawno-Historyczne, 1965)
Recenzja: James Heath, Eighteenth Century Penal Theory, Oxford University Press, 1963, ss. 288.